2014
DOI: 10.1002/2013jc009351
|View full text |Cite
|
Sign up to set email alerts
|

Process modeling studies of physical mechanisms of the formation of an anticyclonic eddy in the central Red Sea

Abstract: Surface drifters released in the central Red Sea during April 2010 detected a well-defined anticyclonic eddy around 23 N. This eddy was 45-60 km in radius, with a swirl speed up to 0.5 m/s. The eddy feature was also evident in monthly averaged sea surface height fields and in current profiles measured on a cross-isobath, shipboard CTD/ADCP survey around that region. The unstructured-grid, Finite-Volume Community Ocean Model (FVCOM) was configured for the Red Sea and process studies were conducted to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 39 publications
8
42
0
Order By: Relevance
“…However, the existence of the Tokar Gap wind jet observed in the MODIS imagery suggests that a simple model for the generation of an eddy dipole caused by surface wind stress [59] may not be appropriate in this situation. More complex models have been able to simulate long-lived anticyclonic eddies in other seasons [78], but the question of why this particular eddy appears to have a cold core in the SST data remains an area for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the existence of the Tokar Gap wind jet observed in the MODIS imagery suggests that a simple model for the generation of an eddy dipole caused by surface wind stress [59] may not be appropriate in this situation. More complex models have been able to simulate long-lived anticyclonic eddies in other seasons [78], but the question of why this particular eddy appears to have a cold core in the SST data remains an area for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous observations in the Red Sea suggest that there is a cyclonic gyre in the northern Red Sea (Morcos and Soliman, 1974;Clifford et al, 1997;and Manasrah, 2004;Chen et al, 2014). The cyclonic gyre is also suggested in satellite SST images.…”
mentioning
confidence: 75%
“…For example, the cyclonic eddy in the northern Red Sea was reproduced by numerical simulations using the Miami Isopycnal Coordinate Ocean Model (MICOM), in an experiment forced only by surface buoyancy loss (Sofianos and Johns, 2003). Chen et al (2014) reproduced the 23°N anticyclonic eddy using the unstructured-grid, Finite-Volume Community Ocean Model 134 (FVCOM). They found that the eddy is formed by seasonally varying buoyancy forcing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many inferences about the general circulation come from numerical simulations (e.g., Clifford et al 1997;Eshel and Naik 1997;Siddall et al 2002;Sofianos et al 2002;Sofianos and Johns 2003;Biton et al 2008Biton et al , 2010Chen et al 2014;Yao et al 2014a,b), most of which reproduce the northernmost gyre but which can differ in other aspects. There have been very few analytical models, laboratory experiments, or idealized numerical simulations apart from the celebrated Phillips (1966) model, but his restriction to a twodimensional overturning cell and his neglect of rotation are limiting.…”
Section: Introductionmentioning
confidence: 99%